Excess Ar in Some Metamorphic and Plutonic Rocks and Reduction of Thermal Neutron-induced ^<40>Ar by Cd Shielding - SAITO Kazuo (Tohoku University, 1994)
It is well known that, by the K-Ar dating, a reliable age cannot be obtained from a sample containing excess Ar. The ^<40>Ar-^<39>Ar method, on the other hand, has, potentially, ability to provive us geologically meaningful ages even for such samples with excess Ar. A Mowson charnockite from Antarctica shows a good example. In the ^<40>Ar-^<39>Ar dating, thermal neutron induced ^<40>Ar from 40K is one of the major source of errors in age calculation. Wrapping a sample with Cd foil is very effective in reducing this disturbing ^<40>Ar.